Military Leadership : In Pursuit of Excellence - Edited By Taylor, Robert L. and Rosenbach, William E.; Foreword by Wakin, Malham M. (Rawalpindi Service Book Club, 2005)
An anthology of classic and contemporary articles, as well as original essays, on leaders, followers, and the personal and organizational values that promote effective military leadership.
Keywords: Leadership -- Command of troops